Some reflections of socio-political changes in Turkey in Vernacular Press in the Archipelago, 1920-1940 - Özay, Mehmet (2023)
Türkiye’s political and social transformations have affected widely influential Islamic institutions in the last centuries. This development is mainly reflected clearly in Islamic and nationalistic views such as independence war, new leadership, victory against the Western nations, the Khilafah issue, the Hijaz affairs, secularization of individual and public life, etc., carried out through direct political means. There was a continuous interest among the journalists, intellectuals, and ulama circles in the Malay Archipelago regarding the developments in the last decades of the Ottoman State and the early period of the newly established Republic of Türkiye in the various vernacular press. These publications in vernacular newspapers, introduced new ideas in the form of both secularization and Pan-Islamism, though contradictory, through coverage of news from Türkiye, which is claimed to have been adopted by the struggle movements in the Archipelago. Revolutionary policies were applied aggressively just after the establishment of the Republic, legitimating the stance of the laic regime and its ideologues and implementers. This led to higher interest among the Malays channeled through vernacular press distributions in the Archipelago, not only as information media but also as ideological vehicles that tried to attain political benefit, as revealed in the case of Asia Minor and its realities within the colonial East Indies. Such interest was driven by a subtle psychological attachment with Türkiye that originated with the Malay communities' acceptance to be ruled under the Caliphate as a highly acclaimed Supreme ruler of the Muslim World. This study examines some vernacular newspapers published in Java and Sumatra Islands in the early decades of the 20th century. It investigates the audiences' dynamics, perspectives, and reactions in the Archipelago towards Türkiye’s socio-political transformation. It exercises the extent of influences this revolutionary period created on the social and religiopolitical changes of the Muslims in the Archipelago. This paper is expected to provide additional narratives of the contribution of vernacular press from Turkey to Nusantara.